(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Seablite or Suaeda maritima (L.) Dumort, a salt marsh plant growing in mangrove forest widely distributed on the landward margin of mangrove habitats of Thai Gulf and Southern of Thailand. Thai traditional medicine is using S. maritima root for abscess healing, allergic symptom relieves and treatment of skin diseases. However, biological properties of S. maritima root are very sparsely reported. In this study was attempt to evaluate antioxidant and anti-inflammation properties besides presence of phytochemicals in S. maritima root. Roots were extracted with 95% ethanol by maceration. Total phenolic content (TPC) and total flavonoid content (TFC) of S. maritima root extract was determined by colorimetric absorbance of reaction mixture measurements. Antioxidant property of S. maritima root extract was evaluated by DPPH, NO radical scavenging and lipid peroxidation inhibition. In vitro anti-inflammation of S. maritima root extract was evaluated by inhibition of NO production of LPS-induced macrophages. TPC and TFC were 37.39±0.46 mg of GAE/g and 67.41±0.27 mg of QE/g, respectively. Extract was strongly inhibited DPPH radical and lipid peroxidation (IC50 = 0.22 ±0.2 and 2.75±0.5 mg/ml). However, S. maritima root extract was poorly inhibited NO radical (IC50 > 1,000 mg/ml). S. maritima root extract was reduced NO production from LPS-induced macrophage cells (20.5±2.8%). There was 0.6 time of anti-inflammation activity from triamcinolone acetonide at same concentration (0.1 mg/ml). Ethanol extract of S. maritima root was contained flavonoids as most of bioactive compounds and possessed preferable in vitro antioxidant and anti-inflammation properties.